2013
DOI: 10.1007/s00253-013-4917-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of novel mutants with an altered gibberellin spectrum in comparison to different wild-type strains of Fusarium fujikuroi

Abstract: The rice pathogen Fusarium fujikuroi is known for producing a wide range of secondary metabolites such as pigments, mycotoxins, and a group of phytohormones, the gibberellic acids (GAs). Bioactive forms of these diterpenes are responsible for hyperelongation of rice stems, yellowish chlorotic leaves, and reduced grain formation during the bakanae disease leading to severely decreased crop yields. GAs are also successfully applied in agriculture and horticulture as plant growth regulators to enhance crop yields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…The presence of GA 4 in CF of both endophytes shows the subsequent conversion of GA 14 and GA 4 on desaturation then yields GA 3 and GA 7 . While GA 1 production is different from them, which is the minor product of 13-hydroxylation of GA 4 and does not convert into GA 3 (Albermann et al 2013;Waqas et al 2014). GC/MS SIM is an established method to identify targeted novel secondary metabolites (Supplementary information 1) and the absence of the GA in the fungal-free culture broth supported our results.…”
Section: Gas Production By Endophytessupporting
confidence: 82%
See 1 more Smart Citation
“…The presence of GA 4 in CF of both endophytes shows the subsequent conversion of GA 14 and GA 4 on desaturation then yields GA 3 and GA 7 . While GA 1 production is different from them, which is the minor product of 13-hydroxylation of GA 4 and does not convert into GA 3 (Albermann et al 2013;Waqas et al 2014). GC/MS SIM is an established method to identify targeted novel secondary metabolites (Supplementary information 1) and the absence of the GA in the fungal-free culture broth supported our results.…”
Section: Gas Production By Endophytessupporting
confidence: 82%
“…During the bioassay, the rice seeds were fully grown on agar water media till the harvest in order to accurately measure the sole effect of fungal CF (Khan et al 2011a(Khan et al , 2011b. Fusarium fujikuroi produces a wide array of diterpenoids including a group of phytohormones mainly GAs (Albermann et al 2013). We compared the effect of CF of wild-type F. fujikuroi with that of our endophytes and found a similar growth-promoting behavior (Hamayun et al 2010;Khan et al 2011aKhan et al , 2011bKhan et al , 2013.…”
Section: Bioactivity Of Endophytesmentioning
confidence: 95%
“…The presence of aforementioned genes involved in the GAs biosynthesis pathway validated the GA producing capability of endophytic P. formosus LHL10. Previously, same GA gene cluster has also been reported in Fusarium fujikuroi , Gibberella fujikuroi , and Fusarium proliferatum (Tudzynski et al, 2001; Albermann et al, 2013; Rim et al, 2013). However, there is no information on GA gene biosynthetic pathway in Paecilomyces sp.…”
Section: Discussionsupporting
confidence: 69%
“…However, recently it was shown that overexpression of hmgR and fppS resulted in a reduced production level, probably due to a negative feedback regulation of HmgR. Subsequent deletion of the transmembrane domains of HmgR, which are known to be responsible for negative feedback regulation by intermediates of sterol biosynthesis, and overexpression of the remaining catalytic domain led to a 2.5-fold increased GA content [ 109 ].…”
Section: The Isoprenoid Pathway: Gibberellinsmentioning
confidence: 99%